Rol de los Padres y el Desarrollo Socioemocional en los niños de 4 años de la Escuela de Educación Básica Particular “Semillitas del Saber" - Herrera Camacho, Mariuxi Yessenia (2024)
This psychopedagogical research focused on strengthening the role of parents in the socio-emotional development of 4-year-old children at the "Semillitas del Saber" private basic education school in Catamayo during the period 2023-2024. The study was designed using an experimental approach, supported by inductive, deductive, analytical and synthetic methods. Tools were used such as an observation sheet and an interview guide for parents. The findings presented diversity in the emotional development of children, evidencing everything from adequate affection to emotional problems related to lack of attachment, difficulties in showing affection and rebellion. Through the application of an activity guide based on Problem-Based Learning (PBL), an increase in the children's sociability, their ability to show affection and their responsibility within the classroom was evident. It is concluded that the different parental roles directly influence the psychological, emotional and affective development of children at an early age, for this reason the present work can be considered for research and future work and it is recommended to expand the line of research in children with dysfunctional and single-parent homes, it is concluded that the different parental roles directly influence the psychological, emotional and affective development of children at an early age, for this reason the present work can be considered for research and future work and it is recommended to expand the line of research in children with dysfunctional and single-parent homes. Keywords: Project Based Learning (PBL), role of parents in socio-emotional development, inadequate process